Emprego da Técnica de pcr em tempo real na detecção de DNA de Brucella spp em lesões de carcaças e vísceras provenientes de matadouros- frigoríficos sob inspeção federal. - SOLA, Marilia Cristina (2011)
Brucellosis is a chronic infectious disease caused by bacterium of the genus Brucella, which affects humans and different species of animals. Despite the implementation of programs aimed at the disease controlling and eradicating, brucelosis is endemic in many countries, especially in developing ones, resulting in significant economic losses and serious implications for animal and public health, due to its zoonotic character. The disease can be transmitted by direct or indirect contact with infected animals, fetal membranes, and also transmitted to humans by contaminated animal products, especially milk and dairy products that have not undergone thermal processing, by raw meat and the handling of carcasses and visceras at the slaughterhouse. The National Programme for Control and Eradication of Brucellosis (PNCEBT), established in the country in 2001, determines the diagnosis of animals in order to establish both the distribution and characterization of the agent. In this context and seeking for a rapid, safe and precise diagnosis of this disease in cattle, we aimed to detect Brucella spp by real time PCR in suspect lesions detected during routine inspection in slaughterhouses under Federal Inspection in the state of Goias, Brazil. Such lesions were related to cervical bursitis, testicular, lung and liver lesions and also in mandibular, retropharyngeal, esophageal, intercostal, apical, mediastinal, tracheobronchial, inguinal, ischiatic, popliteal and mesenteric lymphnodes. In the sampling procedure, cellulose cards were used for storage of biological material (card FTA ® Elute) by impregnating the material in the fibrous matrix of the card. Laboratory analyses were performed on 47 samples from animal tissue and fluids, collected from carcasses and visceras at 40 bovines suspected of brucellosis. Samples were processed at the Laboratório de Biologia Molecular from the Centro de Pesquisa em Alimentos, Escola de Veterinária e Zootecnia from Universidade Federal de Goiás (LBM / CPA / EVZ / UFG). Brucella spp was detected in 42.5% of the bovines with suspect lesions and in 38.3% of samples. It was verified that the use of real-time PCR associated with the FTA® Elute method is an important diagnostic tool in the process of trial and disposition of carcasses and visceras of slaughtered animals and it gives flexibility and efficiency for the diagnosis of diseases, helping the Federal Inspection Service in fulfilling its mission of providing safe food to consumers